2002
DOI: 10.1212/wnl.59.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor fluctuations in Parkinson’s disease

Abstract: Nonmotor fluctuations are frequent and debilitating in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
430
2
13

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(461 citation statements)
references
References 33 publications
16
430
2
13
Order By: Relevance
“…Most patients with PD include fatigue as one of their three most prominent symptoms, and claim that it substantially impacts quality of life [1][2][3][4], yet neurologists tend to underdiagnose fatigue as a presenting symptom of PD [5]. Clinically, fatigue can be described as an "overwhelming sense of tiredness, lack of energy, or feeling of exhaustion" [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with PD include fatigue as one of their three most prominent symptoms, and claim that it substantially impacts quality of life [1][2][3][4], yet neurologists tend to underdiagnose fatigue as a presenting symptom of PD [5]. Clinically, fatigue can be described as an "overwhelming sense of tiredness, lack of energy, or feeling of exhaustion" [6].…”
Section: Introductionmentioning
confidence: 99%
“…Levodopa response fluctuations are not limited to motor symptoms, and most patients with motor fluctuations also experience NMS fluctuations (NMS which worsen in OFF episodes) [66]. Recently, the EuroInf study clearly demonstrated that improvements in dopaminergic responsive NMS (with levodopa and apomorphine infusion) lead to robust improvements in quality of life [67].…”
Section: Management Of Non-motor Complicationsmentioning
confidence: 99%
“…Under blind conditions, a placebo causes no similar mood effect (Maricle et al, 1995b). The extent of mood change does not correlate tightly with the extent of motor improvement or with baseline severity of motor signs (Maricle et al, 1995a(Maricle et al, , 1998Witjas et al, 2002). Finally, patients with rheumatoid arthritis and similar fluctuations in motor disability have significantly less severe fluctuations of mood (Cantello et al, 1986).…”
Section: Introductionmentioning
confidence: 97%
“…Patients consider mood symptoms more disabling than their motor deficits, and caregivers consider them more stressful (Witjas et al, 2002;Carter et al, 2002). Patients with clinically significant mood fluctuations tend to have severe PD, with early onset, long duration of illness, and extremely high rates of psychiatric comorbidity including dementia, prior (nonfluctuating) depression, and drug-induced psychosis (Racette et al, 2002).…”
Section: Introductionmentioning
confidence: 99%